IMPLICATIONS OF UNDERSTANDING LAFADZ BASED WADHIH DILALAH TO THE FORMATION OF LAW ACCORDING TO THE METHOD OF MUTAKALLIMIN AND HANAFI - marzuki, marzuki; Syukri, Rahmat Ilahi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The purpose of this writing is to find out the influence of the opinions of the Hanafi school of thought and the Mutakallimin school of thought about the wadhih dilalah lafadz on the formation of law. This research uses qualitative methods and types of library research, which is a research conducted by conducting library research based on an understanding of the sources related to the theme of this research. To analyse the data that has been collected, the author chooses to use deductive-inductive. The results of this study can be concluded that the Mutakallimin method focuses more on pure theoretical studies to create solid ushul rules, this method emphasises the study of Arabic in depth, using dalalah (indicators) indicated by the lafadz-lafadz or sentences, logical understanding, and proof of the arguments. The Hanafi method in writing ushul fiqh is: too detailed in discussing furu' issues. They laid down the rules of Usul Fiqh by deducing from existing fiqh issues. In formulating the rules of Usul Fiqh, they are heavily influenced by the rules of the Hanafi school. The implications of the understanding between the two opinions about wadhih dilalah resulted in the birth of a variety of different laws